Immunotherapy Efficacy in the Initial Lines of Treatment in Advanced Upper Gastrointestinal Malignancies: A Systematic Review of the Literature. Issue 6 (16th November 2021) - Kamposioras, Konstantinos; Ntellas, Panagiotis; Nikolaou, Michail; Germetaki, Theodora; Gazouli, Ioanna; Dadouli, Katerina; Zarkavelis, George; Amylidi, Anna-Lea; Tolia, Maria; Mauri, Davide
Abstract: Background: The therapeutic role of immune checkpoint inhibitors (ICIs) has represented the cutting edge of clinical research in upper gastrointestinal (GI) malignancies, with these agents now included in the armamentarium of treatment options for advanced gastric and esophageal cancers. Methods: We performed a systematic literature review and pooled analysis to map out the currently available robust clinical evidence for the use of ICIs in upper GI cancers. Immunotherapy (IO), either as monotherapy or in combination with chemotherapy, and its role in first-line, maintenance, and second-line settings, as well as in specific clinical and biological subgroups, were critically appraised. All statistical tests were 2-sided. Results: ICIs, in combination with chemotherapy, have provided statistically significant overall survival benefit in the first-line setting in gastric and gastro-esophageal adenocarcinomas (hazard ratio [HR] = 0.83, 95% confidence interval [CI] = 0.76 to 0.90, P < .001; based on 4 studies) and esophageal squamous cell carcinoma (HR = 0.72, 95% CI = 0.64 to 0.81, P < .001; based on 3 studies), albeit with heterogeneous efficacy according to biomarker expression. Patients with esophageal squamous cell carcinoma, and in particular high programmed cell death ligand-1 expression, derive survival benefit when treated with IO in the second-line setting (HR = 0.74, 95% CI = 0.68 to 0.82, P < .001; for any level of programmed cell death ligand-1 expression). Clinical trials interrogating the combination of IO with chemotherapy in second-line treatment should be seriously considered in upper GI adenocarcinomas. The role of maintenance IO after initial disease control is still unclear and cannot be recommended. Impressive response rates and survival benefit from IO have been reported in patients with microsatellite instability-high tumors (HR = 0.33, 95% CI = 0.19 to 0.57, P < .001), and this warrants further prospective biomarker-driven studies. Conclusions: IO is changing the treatment landscape in upper GI malignancies. The rapidly developing evidence in the field needs to be critically appraised while further validation of the existing information from ongoing trials is awaited.